Failure of Indomethacin and Radiation to Prevent Blast-induced Heterotopic Ossification in a Sprague-Dawley Rat Model. Issue 3 (March 2019) - Robertson, Astor D.; Chiaramonti, Alexander M.; Nguyen, Thao P.; Jaffe, David E.; Holmes, Robert E.; Hanna, E. Lex; Rhee, Juong G.; Barfield, William R.; Fourney, William B.; Stains, Joseph P.; Pellegrini, Vincent D.
Abstract: Background: Although use of nonsteroidal antiinflammatory drugs and low-dose irradiation has demonstrated efficacy in preventing heterotopic ossification (HO) after THA and surgical treatment of acetabular fractures, these modalities have not been assessed after traumatic blast amputations where HO is a common complication that can arise in the residual limb. Questions/purposes: The purpose of this study was to investigate the effectiveness of indomethacin and irradiation in preventing HO induced by high-energy blast trauma in a rat model. Methods: Thirty-six Sprague-Dawley rats underwent hind limb blast amputation with a submerged explosive under water followed by irrigation and primary wound closure. One group (n = 12) received oral indomethacin for 10 days starting on postoperative Day 1. Another group (n = 12) received a single dose of 8 Gy irradiation to the residual limb on postoperative Day 3. A control group (n = 12) did not receive either. Wound healing and clinical course were monitored in all animals until euthanasia at 24 weeks. Serial radiographs were taken immediately postoperatively, at 10 days, and every 4 weeks thereafter to monitor the time course of ectopic bone formation until euthanasia. Five independent graders evaluated the 24-week radiographs to quantitatively assess severity and qualitatively assess the pattern of HO using a modified Potter scale from 0 to 3. Assessment of grading reproducibility yielded a Fleiss statistic of 0.41 and 0.37 for severity and type, respectively. By extrapolation from human clinical trials, a minimum clinically important difference in HO severity was empirically determined to be two full grades or progression of absolute grade to the most severe. Results: We found no differences in mean HO severity scores among the three study groups (indomethacin 0.90 ± 0.46 [95% confidence interval CI, 0.60-1.19]; radiation 1.34 ± 0.59 [95% CI, 0.95-1.74]; control 0.95 ± 0.55 [95% CI, 0.60-1.30]; p = 0.100). For qualitative HO type scores, the radiation group had a higher HO type than both indomethacin and controls, but indomethacin was no different than controls (indomethacin 1.08 ± 0.66 [95% CI, 0.67-1.50]; radiation 1.89 ± 0.76 [95% CI, 1.38-2.40]; control 1.10 ± 0.62 [95% CI, 0.70-1.50]; p = 0.013). The lower bound of the 95% CI on mean severity in the indomethacin group and the upper bound of the radiation group barely spanned a full grade and involved only numeric grades < 2, suggesting that even if a small difference in severity could be detected, it would be less than our a priori-defined minimum clinically important difference and any differences that might be present are unlikely to be clinically meaningful. Conclusions: This work unexpectedly demonstrated that, compared with controls, indomethacin and irradiation provide no effective prophylaxis against HO in the residual limb after high-energy blast amputation in a rat model. Such an observation is contrary to the civilian experience and may be potentially explained by either a different pathogenesis for blast-induced HO or a stimulus that overwhelms conventional regimens used to prevent HO in the civilian population. Clinical Relevance: HO in the residual limb after high-energy traumatic blast amputation will likely require novel approaches for prevention and management.